The Role of Observation in Professional Development in Foreign Language Teacher Education - Barócsi, Stefka (Working Papers in Language Pedagogy, 2007)
The study aims at exploring observation in language classrooms within the context of teacher education, examining how observation can provide student teachers with suggestions for effective teaching and development. The paper looks primarily at the field of Teaching English as a Foreign Language (TEFL) and outlines a qualitative research project which includes ethnographic elements with regard to the teacher trainer who is the researcher in the current situation. The participants are student teachers in the course of teaching practice. The analysis of the data obtained through observation tasks includes the comparison of unstructured and structured observation in the classroom. The findings reveal that teacher trainees can gain substantially from focused observation targeted on particular areas. The study shows the beneficial aspects of this method and also sheds light on its possible integration into the training of prospective teachers.